Counter-hegemonic news - Painter, J (Reuters Institute for the Study of Journalism, Department of Politics and International Relations, University of Oxford, 2008)
This decade has seen the rapid growth of 24-hour television news channels, many with global reach. Some of these aspire to challenge the 'hegemonic' power of the BBC and CNN—charged with propagating a Western viewpoint, masked by claims of impartiality. The debate on impartiality, and on the supposed tyranny of a global narrative controlled by Western broadcasters, is one of the most hotly contested in international journalism today. This pioneering study examines two major and controversial new channels—the world network which is Al Jazeera English and Venezuela’s Telesur. Do they succeed in offering a 'counter-hegemonic' perspective on world news? In what ways is their output different from, and better or worse than, that of the leading Western broadcasters?